Basal Serum Thyroxine Level should Guide Initial Thyroxine Replacement Dose in Neonates with Congenital Hypothyroidism - Ceren Günbey; Alev Özön; E. Nazlı Gönç; Ayfer Alikaşifoğlu; Sevilay Karahan; Nurgün Kandemir (Galenos Yayincilik, 2021)
Objective:Initial high-dose sodium levothyroxine (Na-LT4) (10-15 μg/kg/day) replacement for primary congenital hypothyroidism (CH) is recommended in guidelines. However, high-dose Na-LT4 risks iatrogenic hyperthyroidism. The aim of this study was to investigate the normalizing effect of varying initial doses of Na-LT4 on serum thyroid hormone levels.Methods:Fifty-two patients were analyzed retrospectively. The patients were classified into mild (27/51.9%), moderate (11/21.1%) and severe (14/26.9%) CH, based on initial free thyroxine (fT4) levels. Time taken to achieve target hormone levels was compared within groups.Results:Initial mean Na-LT4 doses for mild, moderate and severe disease were 6.9±3.3, 9.4±2.2 and 10.2±2 μg/kg/day. Serum fT4 levels reached the upper half of normal range (>1.32 ng/dL) in a median of 16, 13 and 16 days in patients with mild, moderate and severe CH with the mean time from initial treatment to first control visit of 14.8±6 days (range 1-36). There was no significant difference in terms of time to achieve target fT4 hormone levels according to disease severity (p=0.478). Seven (25.9%), eight (72.7%) and eight (57.1%) patients experienced hyperthyroxinemia (serum fT4 >1.94 ng/dL) in the mild, moderate, and severe CH groups at the first visit, respectively (p=0.016).Conclusion:Not all patients diagnosed with CH require high-dose Na-LT4. Initial dose of Na-LT4 may be selected on the basis of pretreatment thyroid hormone levels. Some patients with moderate and severe CH, experienced iatrogenic hyperthyroxinemia even though the dose was close to the lower limit of the recommended range in guidelines. We suggest that lower initial doses may be appropriate with closer follow-up within the first week.